Dollar shocks and cross-border capital flows: Evidence from 33 emerging economies - Minjie Hu; Xuemei Yuan (PLoS ONE, 2025)
Under the dollar-dominated international monetary system, the cross-border capital flows of emerging economies reverse sharply following policy shifts by the Fed. To investigate the sensitivity of cross-border capital inflows to dollar shocks, we analyze 33 emerging economies from 2006Q1 to 2021Q4 and use the panel quantile model to explore the dynamic evolution of dollar appreciation shocks at different stages of capital inflows, especially the tail effects. We find that dollar appreciation shocks reduce the total cross-border capital inflows of emerging economies. This impact is mainly through internal and external financial cycle difference channels. Dollar shock impacts differ significantly across different quantiles of capital inflows. Specifically, dollar appreciation shifts the capital inflow to the left and increases the severity of the left-tail risk of capital flows. More flexible exchange rate regimes exacerbate the negative effects of dollar shocks across the distribution of capital inflows. The moderating effect of the fixed exchange rate and intermediate exchange rate systems on external shocks are effective in low quantiles of capital inflows. The sensitivity of “capital flows at risk” to dollar shocks depends on national structural characteristics. As a key risk factor for emerging economies, US dollar appreciation can predict the trend of cross-border capital inflows. Countries should adopt policy measures to curb the adverse effects of US dollar fluctuations.